Tomorrow's Cancer Cures TODAY : 25 secret therapies from around the world - Spreen, Allan, author 644256 (Baltimore, Maryland : Health Sciences Institute, 2012)
Contrary to what we've been told, we are NOT winning the war on cancer. In fact, rates of this terrible disease are rising at a frightening rate across the globe. Even worse, the long-standing, conventional anti-cancer methods (aka: cut, poison, and burn) are "holding actions" at best-and signify the failure of mainstream medicine to really address our health needs and heal cancer. In Tomorrow's Cancer Cures TODAY, Allan Spreen, M.D ., responds to this need for alternatives, sharing a collection of what he's found to be the best and most cutting edge cancer cures from around the world.